2012
DOI: 10.1007/s00520-012-1531-7
|View full text |Cite
|
Sign up to set email alerts
|

Maximal exercise performance in patients with postcancer fatigue

Abstract: Maximal oxygen consumption, a measure for physical fitness, was reduced in severely fatigued compared to non-fatigued cancer survivors. The inferior maximal exercise performance cannot fully be explained by differences in physical activity, self-efficacy, or social support between both groups. Other currently still unknown factors, such as a disturbance in the cardiopulmonary circuit, may play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Patients who undergo cancer treatment frequently report emotional and physical symptoms lasting years after the initial cancer diagnosis, some of which may arise months or years after the treatments are completed. 1012 Comorbid psychological distress is often present and is associated with sociodemographic and cultural factors, in addition to organizational and contextual factors related to where patients receive care. 13 Thus, it is important to improve the ability of medical oncologists to recognize abnormal anxiety and/or depression and to increase the availability of psychological care and supportive and informative facilities for patients throughout their treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who undergo cancer treatment frequently report emotional and physical symptoms lasting years after the initial cancer diagnosis, some of which may arise months or years after the treatments are completed. 1012 Comorbid psychological distress is often present and is associated with sociodemographic and cultural factors, in addition to organizational and contextual factors related to where patients receive care. 13 Thus, it is important to improve the ability of medical oncologists to recognize abnormal anxiety and/or depression and to increase the availability of psychological care and supportive and informative facilities for patients throughout their treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 147 In addition, wearable devices capture physical activity data in continuous, real-time, free-living settings without interrupting participants’ day-to-day. 11 , 17 , 18 , 21-23 , 25 , 40 , 44 , 45 , 51 , 62 , 63 , 66 , 76 , 83 , 85 , 86 , 89 , 90 , 92 , 104 , 108 , 111 , 112 , 119 , 122 , 126 , 128 , 129 , 136 , 139 , 142 , 143 , 147 , 157 , 158 , 161 , 163 , 166 , 172 , 173 , 176-178 , 181 , 188 , 192 , 194 , 208 Of the studies that reported on the adherence of wearable devices, 43 (70%) of them cited high adherence at greater than 80%. Additionally, feasibility studies generally noted positive experience/satisfaction using wearable devices, citing ease of use, comfort, usefulness, and no interference with daily activity related to Fitbits, ActivPal, and Biovotion AG devices.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that fatigued patients may be more prone to initiate a degenerative cycle of physical deconditioning, in which the avoidance of physical activities reduces the cardiorespiratory fitness, which may further deteriorate fatigue complaints (36). Associations are reported between cardiorespiratory fitness and fatigue among several non-stroke patient groups (9)(10)(11)(12). However, research on such relationships post-stroke is limited (8).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting hypothesis is that the presence of fatigue may be a result of impaired cardiorespiratory fitness, triggered by physical deconditioning (6,8). Associations between cardiorespiratory fitness and fatigue have been reported among several non-stroke patient groups (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%